Proceedings of the 2000 ACM Conference on Computer Supported Cooperative Work 2000
DOI: 10.1145/358916.358975
|View full text |Cite
|
Sign up to set email alerts
|

Interaction and outeraction

Abstract: We discuss findings from an ethnographic study of instant messaging (IM) in the workplace and its implications for media theory. We describe how instant messaging supports a variety of informal communication tasks. We document the affordances of IM that support flexible, expressive communication. We describe some unexpected uses of IM that highlight aspects of communication which are not part of current media theorizing. They pertain to communicative processes people use to connect with each other and to manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 623 publications
(80 citation statements)
references
References 25 publications
2
78
0
Order By: Relevance
“…For example, while 'awareness' initially was adopted to denote those practices through which cooperative activities are somehow tacitly and unobtrusively aligned and integrated, some researchers are now using the very same term to conceptualize even the use of instant messaging systems where an actor's deliberately typing and sending a message that then interrupts the flow of activities of other actors is taken as instances of 'awareness' (Nardi et al, 2000).…”
mentioning
confidence: 99%
“…For example, while 'awareness' initially was adopted to denote those practices through which cooperative activities are somehow tacitly and unobtrusively aligned and integrated, some researchers are now using the very same term to conceptualize even the use of instant messaging systems where an actor's deliberately typing and sending a message that then interrupts the flow of activities of other actors is taken as instances of 'awareness' (Nardi et al, 2000).…”
mentioning
confidence: 99%
“…This gives anyone attempting to initiate interaction a degree of plausible deniability concerning whether they intended to initiate an interaction. Plausible deniability of presence or availability has been identified in HCI as a popular benefit of many messaging system features [47]. We use the term more in the spirit of Pinker's explanation of the utility of "indirect speech" [52].…”
Section: Principle 2: Ambiguity Of First Move -Provide Plausible Denimentioning
confidence: 99%
“…In addition, IM study participants reported the ability to negotiate their availability through postponing conversations, and these findings support earlier studies suggesting IM is less intrusive than traditional communication methods for determining availability of coworkers. 6 A number of research studies show that IM improves teamwork and is useful for discussing complex tasks. Huang, Hung, and Chen compared the effectiveness of email and IM and the number of new ideas; they found that groups utilizing IM generated more ideas than the email groups.…”
Section: Instant Messaging In the Workplacementioning
confidence: 99%